Challenges Malaysian teachers face in the inclusion of autistic students in the normal classroom - Mohd Zuki, Nurul Husna; Nik Abdul Rahman, Nik Suryani (Zes Rokman Resources, 2016)
As every student has equal right for being educated in the mainstream classroom settings, inclusive education has been introduced in public schools all around the globe. Lack of professional skill and knowledge was one of the barriers faced by teachers as reported in the literatures (Sharma, Moore & Sonawane, 2009; ul Hassan, Parveen & Riffat-un- Nisa, 2010; Wehbi, 2006; Fakolade & Adeniyi, 2009; Agbeneyga, 2007, as cited in Ballhysa & Flagler, 2011). The aim of this study is to explore the challenges that Malaysian teachers faced when having autistic students in the inclusive program. The present study employed a qualitative research method with case study design through face-to-face interviews with five general classroom teachers from a secondary school in Kuala Lumpur. A self-developed instrument with 11 interview questions was used as an interview guide. Six major themes were found through thematic analysis: student’s behavioral problem, student’s cognitive problem, and environmental problem represented the challenges that Malaysian teachers faced when having autistic students in the normal classroom, while skillfulness, receptiveness, and environmental assistance represented the ways Malaysian teachers coped with the inclusive environment. The result of present study may help general classroom teachers who lack skills and knowledge on the inclusive education and help them to fulfill the needs of students with autism and mainstream students. All in all, this study is suitable for not only to people in education but also to other kind of field works such as psychology and sociology.